Job Stress as a Mediating Variable: Can Work-Life Balance Improve the Performance of Generation Z Employees in IT Consulting Companies? - Oedi Niesya Bella Ragazza; Djudiyah Djudiyah; Yuni Nurhamida (About the Journal, 2026)
In a dynamic IT development work environment, Generation Z employees face high demands for preparedness and adaptation, which has the potential to increase work stress and have an impact on decreased performance, especially when work-life balance is not optimally met. This study aims to examine the effect of work-life balance on employee performance, with work stress as a mediator. Participants in this study were 194 generation Z employees in IT development companies who were selected using a total sampling technique. There are three scales used in this study: the Individual Work Performance Scale (IWPQ), the Work-life Balance Scale, and the Job Stress Scale (JSS). Data analysis used Hayes' mediated regression analysis model 4 in the SPSS application. The results of the study indicate that work stress partially mediates the influence between work-life balance and employee performance. The results of the analysis indicate that work-life balance has a significant effect on employee performance, both directly and indirectly through work stress. This means that work stress has been proven to play a partial mediation role between work-life balance and employee performance.Dalam lingkungan kerja IT development yang dinamis, karyawan generasi Z menghadapi tuntutan kesiapsiagaan dan adaptasi yang tinggi, yang berpotensi meningkatkan stres kerja dan berdampak pada penurunan kinerja, terutama ketika work-life balance tidak terpenuhi secara optimal. Penelitian ini bertujuan untuk menguji pengaruh work-life balance terhadap kinerja karyawan, dengan stres kerja sebagai mediasi. Partisipan pada penelitian ini adalah 194 karyawan generasi Z pada perusahaan IT development yang diambil dengan teknik total sampling. Ada 3 skala yang digunakan pada penelitian ini yaitu Skala Individual Work Performance (IWPQ), Work-life Balance Scale dan Skala Job Stress Scale (JSS). Analisis data menggunakan mediated regression analysis model 4 dari Hayes pada aplikasi SPSS. Hasil penelitian menunjukan bahwa stres kerja memediasi secara parsial pengaruh antara work-life balance dan kinerja karyawan. Hasil analisis menunjukkan bahwa work-life balance berpengaruh signifikan terhadap kinerja karyawan, baik secara langsung maupun tidak langsung melalui stres kerja. Artinya, stres kerja terbukti berperan sebagai mediasi parsial antara work-life balance dan kinerja karyawan.